Influência da cigarrinha-das-raízes (Mahanarva fimbriolata) e da adubação na qualidade do caldo e da cana-de-açúcar - Pavão, Marcos Antônio (2012)
Brazil is the world's largest producer of sugar, a product whose specifications are somewhat dictated by the market. One of the important characteristics for sugar relates to its color. Sugars with less color index represent greater value and are preferred by buyers. Manufacturing a white crystal sugar with low cost need is a good quality raw material. The attack of pests and plant nutritional imbalance can interfere with the quality of raw material. The aim of this study was to evaluate the influence of organic fertilization, lack of fertilizer and root infestation by froghoppers in the production of substances that may compromise the quality of the broth, as result of in the defense system of the plant, with can interfere in the quality of juice. The experiment was conducted between the months of July 2010 to December 2011. A variety RB72454 was grown in pots of 50 liters in a randomized block design in split-split with six treatments: i) mineral fertilizer without froghopper ii) mineral fertilizer plus froghopper iii) organic compound without froghopper iv) organic compound froghopper v) without fertilization without froghopper and vi) no fertilization with froghopper; all treatments had four replicates and three harvest seasons. The samples were determined for BRIX, cane pol, pol juice, purity, reductor sugars (cane AR and AR juice), fiber, total reducing sugars (ART), starch, and phenolics. Data were subjected to analysis of variance and the test of Scott-Knott 5%. The results showed that the infestation of froghopper-roots in plots with mineral fertilizer and without fertilizer increased the content of phenolic compounds, compared to treatments without the presence of the insect. Plants from cane sugar fertilized with organic compost produced broth with lower content of phenolic compounds in presence with the absence of the insect. The infestation of leafhopperroots apparently caused greater amount of starch in the broth.